Preparation and characterization of Styrene-Methyl Methacrylate in Deproteinized Natural Rubber Latex (SMMA-DPNR) - Che Man, Siti Hajjar; Hashim, Azanam; Md. Akil, Hazizan (2006)
The graft polymerization of Styrene and Methyl Methacrylate (MMA) onto deproteinized natural rubber latex (SMMA-DPNR) was carried out using ammonium peroxy disulfate (N2H8O8S2) as an initiator. The suitable reaction conditions based on the higher monomer conversion was determined. The SMMA-DPNR at 6 hours reaction time was successfully prepared with degree of conversion more than 99 %. The copolymers composition of the resultant SMMA-DPNR was obtained using 1H-NMR Spectroscopy. As expected, composition of styrene in DPNR was higher than that of MMA due to the higher reactivity ratio of styrene monomer as compared to MMA monomer and the structure of the NR backbone.